The Green Innovation Effect on Heavy-Polluting Enterprises Under the Environmental Protection Law - Ouyang, Leqian; You, Daming (Frontiers in Energy Research, 2021)
One of the main purposes of the 2015 Environmental Protection Law (EPL) of the People's Republic of China is to boost the green innovation of the enterprises. Using heavy-polluting enterprises as examples, this paper uses the Difference-in-difference analysis (DDD) technique to analyze the influence of EPL on the green innovation of enterprises under fiscal decentralization and enterprise heterogeneity. Results show that EPL exerts a negative impact on the green innovation of heavy-polluting enterprises at the national level, as well as those in the central and western areas specifically. The only presence of positive motivation for green innovation is being found in the eastern area, although, the motivation seems to be insignificant. The negative impacts have been lasting in the long run, especially for the low-performance enterprises in the central areas. As for the targeted implementation of EPL in China, local governments should make the best use of financial power under fiscal decentralization. This balanced approach is designed to motivate enterprises in different regions with various performance levels to develop green innovation based on their different weaknesses and strengths.